Habitat degradation and trout stocking can reinforce the impact of flash floods on headwater specialist Alpine bullhead Cottus poecilopus – A case study from the Carpathian Mountains. (10th March 2018) - Kubín, M.; Rulík, M.; Lusk, S.; Závorka, L.
Summary: In freshwater streams, flooding is a typical source of natural disturbance that plays a key role in the dynamics of animal populations and communities. However, habitat degradation and fish stocking might increase the severity of its impact. We tested the effects of a flash flood on the abundance of three size classes of headwater dwelling Alpine bullhead, Cottus poecilopus, in the streams of the Carpathian Mountains in the Czech Republic, that are stocked with hatchery‐reared brown trout, Salmo trutta . We showed that the overall abundance of Alpine bullhead was highest at the sites with the least degraded habitat (i.e., natural habitat) and we caught almost no Alpine bullhead at the sites with the most degraded habitat. The flash flood had a strong negative effect on the abundance of the largest individuals of Alpine bullhead. Abundance of small and medium size Alpine bullhead was negatively affected by the abundance of adult stocked brown trout before as well as after the flash flood. However, negative effect of adult brown trout abundance on abundance of large Alpine bullhead was not significant before the flash flood, and it became significant after the flash flood. This could indicate an accumulation of negative impacts of trout stocking and flash flood on this size class. Overall, our results suggest that stocking of hatchery trout and habitat degradation can reinforce the impact of flash floods on the population of Alpine bullhead in the streams of the Carpathian Mountains.